Głos PANu . pismo NSZZ "Solidarność" w Polskiej Akademii Nauk, no. 11, 1981 - [EIC Jan Środoń] ([s.n.], 1981)
Creation and circulation: For trade-union use; From issue no. 10(1981) countrywide publication of Polish Academy of Sciences